An Alcohol Dehydrogenase from the Short‐Chain Dehydrogenase/Reductase Family of Enzymes for the Lactonization of Hexane‐1, 6‐diol. (30th October 2018) - Dithugoe, Choaro D.; van Marwijk, Jacqueline; Smit, Martha S.; Opperman, Diederik J.
Abstract: Biocatalytic production of lactones, and in particular ϵ‐caprolactone (CL), have gained increasing interest as a greener route to polymer building blocks, especially through the use of Baeyer–Villiger monooxygenases (BVMOs). Despite several advances in the field, BVMOs, however, still suffer several practical limitations. Alcohol dehydrogenase (ADH)‐mediated lactonization of diols in turn has received far less attention and very few enzymes have been identified for the conversion of diols to lactones, with horse‐liver ADH (HLADH) remaining the catalyst of choice. Screening of a diverse panel of ADHs, Aa SDR‐1, a member of the short‐chain dehydrogenase/reductase family, was found to produce ϵ‐caprolactone from hexane‐1, 6‐diol. Moreover, cofactor regeneration by an NADH oxidase eliminated the requirement of co‐substrates, yielding water as the sole by‐product. Despite lower turnover frequencies as compared to HLADH, higher selectivity was found for the production of CL, with HLADH forming significant amounts of 6‐hydroxyhexanoic acid and adipic acid through aldehyde dehydrogenation/oxidation of the gem ‐diol intermediates. Also, CL yield were shown to be dependent on buffer choice, as structural elucidation of a Tris adduct confirmed the buffer amine to react with aliphatic aldehydes forming a Schiff‐base intermediate which through further ADH oxidation, forms a tricyclic acetal product. Abstract : Born to be mild : A short‐chain dehydrogenase/reductase catalyzes the oxidative lactonization of hexane‐1, 6‐diol to ϵ‐caprolactone, with only water as by‐product when using NADH‐oxidase for co‐factor regeneration. ϵ‐Caprolactone yields are significantly affected by buffers containing primary amines, resulting in irreversible adducts with aldehyde intermediates.